1987
DOI: 10.1210/endo-120-4-1422
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for a Direct in Vitro Action of Sex Steroids on Rabbit Cartilage Cells during Skeletal Growth: Influence of Age and Sex*

Abstract: A direct effect of sex steroid hormones on in vitro cartilage cell metabolism was demonstrated. Cells were derived from rabbit fetuses on day 20 of gestation, and from male and female rabbits aged from 2 to 80 days. Testosterone (T), dihydrotestosterone (DHT), or 17 beta-estradiol (E2) (10(-9) -10(-9) M) were added to primary culture of epiphyseal articular chondrocytes. They showed an age-dependent stimulatory effect on [35S]sulfate incorporation into newly synthesized proteoglycans. In cultured rabbit fetal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
32
0
2

Year Published

1992
1992
2004
2004

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 120 publications
(38 citation statements)
references
References 31 publications
4
32
0
2
Order By: Relevance
“…The findings indicate that both ER subtypes are expressed in resting and proliferative chondrocytes from birth through sexual maturation in both rats and rabbits. This hypothesis is consistent with previous in vivo (Strickland & Sprinz 1973, Jansson et al 1983 and in vitro (Corvol et al 1987, Blanchard et al 1991) studies, which suggests that estrogen acts directly on growth plate chondrocytes. Our findings are also consistent with a study performed by Gunther et al (1999), who used an ER antagonist to block estrogen-induced acceleration of skeletal development in a mouse model.…”
Section: Discussionsupporting
confidence: 93%
“…The findings indicate that both ER subtypes are expressed in resting and proliferative chondrocytes from birth through sexual maturation in both rats and rabbits. This hypothesis is consistent with previous in vivo (Strickland & Sprinz 1973, Jansson et al 1983 and in vitro (Corvol et al 1987, Blanchard et al 1991) studies, which suggests that estrogen acts directly on growth plate chondrocytes. Our findings are also consistent with a study performed by Gunther et al (1999), who used an ER antagonist to block estrogen-induced acceleration of skeletal development in a mouse model.…”
Section: Discussionsupporting
confidence: 93%
“…This may be in line with our study, since OVX decreased the cell diameter in the proliferating zone, despite an increase in its width, indicating that matrix synthesis is downregulated when estrogen is deficient. In contrast, it has been shown that E 2 stimulates 35 S uptake by chondrocytes, implying increased chondrocyte differentiation (Corvol et al 1987, Blanchard et al 1991). An explanation for a reduced width of the hypertrophic zone could be that estrogen causes the rate of apoptosis or vascular invasion to exceed the rate of cartilage matrix synthesis (Turner & Evans 2000).…”
Section: Discussionmentioning
confidence: 96%
“…While the growth-promoting effect of testosterone has been shown in humans (Attie et al 1990, Keenan et al 1993, and supported by observations on its direct effect on rabbit epiphyseal articular chondrocytes (Corvol et al 1987) and rat tibial EGP width (Ren et al 1989), the precise mechanism(s) of testosterone action is elusive. We found no change in hepatic IGF-I mRNA levels in response to testosterone administration, either over 12 h post injection, or after 10 days of continuous exposure to testosterone.…”
Section: Discussionmentioning
confidence: 99%